2019
DOI: 10.1055/s-0039-3401818
|View full text |Cite
|
Sign up to set email alerts
|

The Distance between the Pectoralis Major Tendon Insertion and the Top of the Humeral Head is a Reliable Landmark: An Anatomic Study

Abstract: Purpose This study aimed to analyze the distance between the superior edge of the pectoralis major and the top of the humeral head and evaluate whether this distance is a consistent measurement. Methods Twenty-two shoulders in eleven cadavers were dissected and the attachment of the pectoralis major tendon was preserved. Two distances were recorded with the help of digital vernier caliper: the distance between the upper edge of pectoralis major and tangent to the top of humeral head (PM–T) and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A previous anatomical analysis reported that the superior margin of the humeral head articular surface is normally superior to the top of the greater tuberosity by 5-10 mm. 17 , 21 As per these reports, we defined malalignment as HHH <0 mm or >10 mm (poor HHH) and the anatomical HHH as that between 0 mm and 10 mm (good HHH).
Figure 2 X-ray images of the humeral head.
…”
Section: Methodsmentioning
confidence: 99%
“…A previous anatomical analysis reported that the superior margin of the humeral head articular surface is normally superior to the top of the greater tuberosity by 5-10 mm. 17 , 21 As per these reports, we defined malalignment as HHH <0 mm or >10 mm (poor HHH) and the anatomical HHH as that between 0 mm and 10 mm (good HHH).
Figure 2 X-ray images of the humeral head.
…”
Section: Methodsmentioning
confidence: 99%
“…The important of intraoperatively restoring anatomic humeral height, humeral version, and tuberosity reconstruction were highlighted to improve outcomes after hemiarthroplasty for shoulder fracture (9,10).The nonanatomic reduction of the tuberosity in the horizontal may result in insurmountable postoperative motion restriction (11). There are some published methods of restoring the appropriate humeral length for arthroplasty, such as preoperative plan according to the calcar of non-injured extremity, landmark using medial calcar of proximal humeral fracture, reference using pectoralis major tendon, and the Gothic arch based on radiographs (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The important of intraoperatively restoring anatomic humeral height, humeral version, and tuberosity reconstruction were highlighted to improve outcomes after hemiarthroplasty for shoulder fracture (9,10).The nonanatomic reduction of the tuberosity in the horizontal may result in insurmountable postoperative motion restriction (11). There are some published methods of restoring the appropriate humeral length for arthroplasty, such as preoperative plan according to the calcar of non-injured extremity, landmark using medial calcar of proximal humeral fracture, reference using pectoralis major tendon, and the Gothic arch based on radiographs (12)(13)(14). However, there are some obstructions during surgery: preoperative anteroposterior radiographs of the injured and the contralateral humerus, the break off of pectoralis major tendon for exposure of fracture, repeated intraoperative radiographs.…”
Section: Introductionmentioning
confidence: 99%